The effects of construal level and donation magnitude: the case of cause-related marketing - Phang Ing @ Grace; Lin, Hsin Yin; Lim, Tze Yin (MAG Scholar, 2020)
Marketers are focusing on their corporate social responsibility in recent years, utilizing charity business as an effective sale and marketing strategy. A better understanding of consumer behaviour in relation to cause-related marketing (CRM) is critical, as both marketers and consumers are able to build a win-win relationship. Borrowing the construal level theory, we examined the effects of advertising framing in CRM, focusing on how construal level and donation magnitude could have affected consumer’s attitude and willingness to donate. The study proposes that words induce high construal level that consumers should have higher buying intention and willingness to participate in a word- vs. picture-based advertisement. Consistent with the previous study, the preliminary study had successfully attributed picture vs. words to low vs. high construal level. However, the main study results failed to indicate a higher intention to participate and to buy among consumers in a high (e.g. 25% of the selling price) vs. low donation magnitude (e.g. 5% of the selling price) condition. The contribution of the current study is expected to extend the construal level theory by assessing the donation magnitude, which affecting consumer behaviour in the marketing context. The findings of the studies added to the understanding of construal level and donation magnitude manipulations in CRM, which benefits both the CRM marketers as well as the academic researchers. Besides, this study also demonstrated the potential to develop brand awareness, promote a social cause and inspire consumers to demonstrate support for causes they concern about.